The Image od Frederick II of Swabia: A Review - Vagnoni, Mirko (Eikón / Imago, 2013)
The historians have often seen, maybe with too much enthusiasm, the representation of Frederick II of Swabia in a large number of works of art. Reviewing supposed and real pictures of the Swabian in sphragistics, numismatic, glyptic, jewelry, sculpture, painting and miniature, in this paper we delineate the Status quaestionis on the portraiture of Frederick II, trying to outline which were his own images produced in his court and under his own initiative. Thus we will arrive, after a route to the exclusion that will leave very few specimens, to track down the official portraits that the Stupor mundi wanted to give of himself and that are still preserved.